2015
DOI: 10.1088/1009-0630/17/9/05
|View full text |Cite
|
Sign up to set email alerts
|

Study of Non-Thermal DC Arc Plasma of CH4/Ar at Atmospheric Pressure Using Optical Emission Spectroscopy and Mass Spectrometry

Abstract: Non-thermal C/H/Ar plasmas are widely applied to carbonaceous material production and processing. In this work, plasma parameters and gaseous species of the atmospheric non-thermal C/H/Ar plasmas produced by an atmospheric-pressure DC arc discharge generator in CH4/Ar were investigated. The voltage-current characteristics were measured for different CH4/Ar ratios. Optical emission spectroscopy was employed to analyze the electron excitation temperature, gas temperature and electron density under various discha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Liao et al observed a large number of C x H y (x 10, y 12) fragment mass peaks from a DC arc Ar-CH 4 plasma operating at a gas temperature >2800 K and at a high CH 4 concentration ( 2%). They also obtained emission spectra but the only molecular derived features observed were weak CH(A-X) and H β lines and stronger lines representing H α and C 2 swan systems [21]. Therefore, we can expect trace methane in our plasma to remain predominantly in molecular form, with dissociated fragments at sub-ppm concentrations.…”
Section: Discussionmentioning
confidence: 84%
“…Liao et al observed a large number of C x H y (x 10, y 12) fragment mass peaks from a DC arc Ar-CH 4 plasma operating at a gas temperature >2800 K and at a high CH 4 concentration ( 2%). They also obtained emission spectra but the only molecular derived features observed were weak CH(A-X) and H β lines and stronger lines representing H α and C 2 swan systems [21]. Therefore, we can expect trace methane in our plasma to remain predominantly in molecular form, with dissociated fragments at sub-ppm concentrations.…”
Section: Discussionmentioning
confidence: 84%
“…The 2λ method (i.e. the relative intensity ratio of two spectral lines) was used to calculate the T e in non-thermal plasma [ [21][22][23][24]. The T e can be deduced from the relation between two excitation levels of O atoms by equation (1).…”
Section: T E Measurementmentioning
confidence: 99%
“…Also, it provides an estimation of the vibrational temperature of species and background gas temperature based on the rotational branch of spectral lines and information relating to the plasma chemistry and substances present in the plasma [26] . Optical emission diagnosis of methane plasma has intensively been investigated in the literature [27][28][29][30][31] . Bai et al studied the reaction mechanism in nonthermal plasma-assisted methane conversion performed by different sources [27] .…”
Section: Introductionmentioning
confidence: 99%